Estimating transmissivity from single‐well pumping tests in heterogeneous aquifers. Issue 1 (28th January 2016) - Pechstein, Armin; Attinger, Sabine; Krieg, Ronald; Copty, Nadim K.
Abstract: Although aquifers are naturally heterogeneous, the interpretation of pumping tests is commonly performed under the assumption of aquifer homogeneity. This yields interpreted hydraulic parameters averaged over a domain of uncertain extent which disguises their relation to the underlying heterogeneity. In this study, we numerically investigate the sensitivity of the transient drawdown at the pumping well, to nonuniform distributions of transmissivity in confined aquifers. Frechet kernels and their time derivative are used to estimate two spatially averaged transmissivities, denoted the equivalent and interpreted transmissivity, T eq and T in, respectively, for the case of single‐well pumping tests. Interrelating T eq and T in is achieved by modeling T in in terms of a distance dependent, radially heterogeneous field. In weakly heterogeneous aquifers, T eq approximates T PW, the local transmissivity at the pumped well. With increasing degree of heterogeneity, T eq deviates from T PW as pumping propagates. T in starts at T PW, approaching the spatial geometric mean of transmissivity during late pumping times. Limits of the proposed spatial weighting functions are investigated by treating the interpreted storativity, S est, as an indicator for flow connectivity. It is shown numerically that the spatial weights for T eq and T in agree well to the underlying heterogeneity if S est < 1 . Finally, implications for applying the concepts of T eq and T in to heterogeneous domains, and, for real world applications are discussed. It is found that time‐dependent spatial averages of T in agree well with estimates of the interpreted transmissivity from the Continuous‐Derivation method. Key Points: Frechet kernels are used to derive spatial weighting functions for transmissivity Time derivative of the drawdown from pumping tests allows for characterizing aquifer heterogeneity Impact of flow connectivity cannot generally be captured by spatial weighting of transmissivity